Indigenous Pacific Approaches to Climate Change Aotearoa/New Zealand - Carter, Lyn (Palgrave Studies in Disaster Anthropology, 2019)
"A key text for climate change, New Zealand Studies, Māori Studies, and Indigenous Studies, for both academics and a wider readership interested in these debates. Lyn Carter skillfully moves through a wide range of issues, providing a discussion that is focused, fresh, original, and accessible." -Ian Conrich, Professorial Fellow, University of Vienna, Austria Situating Māori Ecological Knowledge (MEK) within traditional environmental knowledge (TEK) frameworks, this book recognizes that indigenous ecological knowledge contributes to our understanding of how we live in our world (our world views), and in turn, how we adapt to climate change. As an industrialized nation, Aotearoa/New Zealand (A/NZ) has responsibilities and obligations to other Pacific dwellers, including its indigenous populations. In this context, Lyn Carter discusses how A/NZ can benefit from the wider Pacific strategies already in place; how to meet its global obligations to reducing greenhouse gases; and how A/NZ can utilize MEK to achieve substantial inroads into long-term adaptation strategies and sustainable practices. Carter demonstrates that in all respects Māori tribal groups are well-placed to be key players: adaptation strategies, policies, and practices are integrated throughout Māori/Iwi traditional knowledge. Lyn Carter is Senior Lecturer in Te Tumu (the School of Māori, Pacific and Indigenous Studies) at the University of Otago, New Zealand. .